Pengaruh Employee Engagement dan Disiplin Kerja terhadap Kinerja Karyawan pada PT. Mertha Buana Motor Singaraja - Komang Serly Tikarani; I Nyoman Sujana (Fakultas Ekonomi Universitas Pendidikan Ganesha, 2026)
This study aims to determine: (1) the positive and significant effect of employee engagement on employee performance at PT Mertha Buana Motor Singaraja, and (2) the positive and significant effect of work discipline on employee performance at PT Mertha Buana Motor Singaraja. (3) The positive and significant influence of employee engagement and work discipline simultaneously on employee performance at PT. Mertha Buana Motor Singaraja. The population in this study was all 40 employees at PT. Mertha Buana Motor Singaraja, and the sample in this study was all 32 employees in the sales and mechanics departments. The sampling technique in this study was purposive sampling. The research results show that : (1) there is a positive and significant influence of employee engagement on employee performance at PT Mertha Buana Motor Singaraja, (2) there is a positive and significant influence of work discipline on employee performance at PT Mertha Buana Motor Singaraja, (3) there is a simultaneous influence of employee engagement and work discipline on employee performance at PT Mertha Buana Motor Singaraja.